Evaluation of the effects of lumbosacral dorsal root ganglion pulsed radiofrequency treatment applied via a caudally inserted flexible electrode in radicular pain due to lumbar foraminal stenosis - Ender Sir; Alp Eren Çelenlioğlu; Ezgi Can; Gül Didem Batur Sir; Münevver Ece Güven (PLoS ONE, 2025)
Background This retrospective study aimed to evaluate the effects of unilateral lumbosacral dorsal root ganglion (DRG) pulsed radiofrequency (PRF) treatment administered via a caudally inserted electrode to patients with unilateral lumbar radicular pain (LRP) due to foraminal stenosis. Methods The study cohort included 80 patients. Patients were evaluated using the numeric rating scale (NRS) and modified Oswestry disability index (MODI) at pre-, 3 weeks, and 6 months postprocedure. Patients were retrospectively divided into three groups based on their lumbar surgery history: those without a lumbar surgery history (group N), those who underwent discectomy surgery (group D), and those who underwent lumbar stabilization surgery (group S). Treatment success was defined as a ≥ 50% decrease in pain scores at 6 months. Results NRS and MODI scores were significantly decreased at all follow-ups ( P < 0.001). Treatment success (≥50% reduction in NRS scores) at 6-month follow-up was 53.6% in the cohort (group N, 75%; group D, 61.5%; group S, 30.8%; P = 0.004). In group N, decreased NRS and MODI scores were more significant than those with a history of surgery, with the procedure duration being shorter. Conclusions DRG PRF administered caudally is an effective, safe method in patients with refractory LRP due to foraminal stenosis. Specifically, it provides convenience on patients with instrumentation-related imaging difficulties or those with anatomic disorders such as lordosis, large osteophytes, and severe rotation. In addition, this treatment method can be preferred due to its advantages such as reaching multiple DRG levels with a single needle entry, applying PRF and direct drug injection to the epidural space.